DNA polymorphisms of aSI casein among zebu cattle and Murrah buffaloes by allele-specific polymerase chain reaction (ASPCR) - SHANKER, V; BHATTIA, S (The Indian Journal of Animal Sciences, 2013)
Genotype variants of B and C alleles of asI-casein milk protein (locus) were identified in Indian Sahiwal (62), and Tharparkar cattle ( 25) and Murrah buffaloes (68) using genomic DNA from blood samples and rapid, powerful technique of allele specific polymerase chain reaction (ASPCR). C allele was more frequent in animals of both the species. Absence of both variants B and G in 6.5 % of Sahiwal, 8% of Tharparkar and 8.8 % of Murrah buffaloes screened, suggested the possibility of presence of either an additional new allele or a rare allele.